Differences in root phenology and water depletion by an invasive grass explains persistence in a Mediterranean ecosystem. Issue 9 (9th September 2019) - Phillips, Michala L.; McNellis, Brandon E.; Allen, Michael F.; Allen, Edith B.
Abstract : Premise: Flexible phenological responses of invasive plants under climate change may increase their ability to establish and persist. A key aspect of plant phenology is the timing of root production, how it coincides with canopy development and subsequent water‐use. The timing of these events within species and across communities could influence the invasion process. We examined above‐ and belowground phenology of two species in southern California, the native shrub, Adenostoma fasciculatum, and the invasive perennial grass, Ehrharta calycina to investigate relative differences in phenology and water use. Methods: We used normalized difference vegetation index (NDVI) to track whole‐canopy activity across the landscape and sap flux sensors on individual chaparral shrubs to assess differences in aboveground phenology of both species. To determine differences in belowground activity, we used soil moisture sensors, minirhizotron imagery, and stable isotopes. Results: The invasive grass depleted soil moisture earlier in the spring and produced longer roots at multiple depths earlier in the growing season than the native shrub. However, Adenostoma fasciculatum produced longer roots in the top 10 cm of soil profile in May. Aboveground activity of the two species peaked at the same time. Conclusions: The fact that Ehrharta calycina possessed longer roots earlier in the season suggests that invasive plants may gain a competitive edge over native plants through early activity, while also depleting soil moisture earlier in the season. Depletion of soil moisture earlier by E. calycina suggests that invasive grasses could accelerate the onset of the summer drought in chaparral systems, assuring their persistence following invasion.